2016
DOI: 10.3390/ma9050318
|View full text |Cite
|
Sign up to set email alerts
|

SEM, EDS and XPS Analysis of the Coatings Obtained on Titanium after Plasma Electrolytic Oxidation in Electrolytes Containing Copper Nitrate

Abstract: In the paper, the Scanning Electron Microscopy (SEM) with Energy Dispersive X-ray Spectroscopy (EDS) and X-ray Photoelectron Spectroscopy (XPS) results of the surface layer formed on pure titanium after plasma electrolytic oxidation (micro arc oxidation) at the voltage of 450 V are shown. As an electrolyte, the mixture of copper nitrate Cu(NO3)2 (10–600 g/L) in concentrated phosphoric acid H3PO4 (98 g/mol) was used. The thickness of the obtained porous surface layer equals about 10 μm, and it consists mainly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 38 publications
3
44
0
Order By: Relevance
“…The studies already carried out by the authors have shown that it is possible to obtain porous PEO coatings which are enriched only with copper [28] or calcium [29]. In addition, in reference to [13], new coatings obtained in electrolyte contacting two nitrates (Zn(NO 3 ) 2 ·6H 2 O, Mg(NO 3 ) 2 ·6H 2 O) were presented.…”
Section: Electrolytesmentioning
confidence: 99%
“…The studies already carried out by the authors have shown that it is possible to obtain porous PEO coatings which are enriched only with copper [28] or calcium [29]. In addition, in reference to [13], new coatings obtained in electrolyte contacting two nitrates (Zn(NO 3 ) 2 ·6H 2 O, Mg(NO 3 ) 2 ·6H 2 O) were presented.…”
Section: Electrolytesmentioning
confidence: 99%
“…17,No. 4 (54), December 2017 In Figure 8, 2D roughness parameters (Ra, Rz, Rz ISO − it is possible to obtain porous coatings containing calcium and phosphorus on titanium substrate by plasma electrolytic oxidation at voltages of 450 V to 650 V in an electrolyte based on concentrated phosphoric acid H 3 PO 4 and calcium nitrate Ca(NO 3 ) 2 ·4H 2 O − the chemical composition of the PEO porous coatings depends on the PEO voltage; the higher voltage, the more calcium in the PEO coating is obtained − Ca/P ratio increases linearly with increasing voltage from 450 V to 650 V − the surface roughness of the porous coatings depends on the PEO voltage; with PEO voltage increasing, the surface roughness increases, too − PEO treatment with potential of 650 V results in obtaining the surface roughness which is approximately twice as high in comparison with that one recorded for the coating obtained at 450 V.…”
mentioning
confidence: 99%
“…In the last two decades, plasma electrolytic oxidation (PEO) became one of the most attractive surface treatment methods of advanced ceramic coating formation on metallic compounds [1][2][3][4][5]. This technological approach is usually applied in so-called valve metals as aluminum, magnesium, or titanium to obtain surface advanced properties such as high electrical insulation, corrosion and wear resistance, and excellent performance [6][7][8].…”
Section: Introductionmentioning
confidence: 99%